THE IMPORTANCE OF STEAM EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
STEAM- represents the integrative approach of education with scientific-research, technical development concepts of everyday life. The purpose of such an approach is to promote scientific literacy and competitiveness by involving the school and the public in ensuring the sustainable development of the world's development and economy through education.